Sutureless Approach for Gastroschisis Patients in Palestine - Yousef S. Abuzneid; Sadi A. Abukhalaf; Duha Rabi; Abdelrahman Rabee; Safwan Mashhour; Radwan Abukarsh (Case Reports in Surgery)
Gastroschisis is a ventral abdominal wall congenital defect with bowel herniation outside the abdominal cavity. Gastroschisis traditional management is the primary operative closure surgery (POCS), but the sutureless silo approach (SSA), a novel alternative, gains wide acceptance in the developed countries and across nations. This study describes the first-ever gastroschisis patient managed with the sutureless silo approach in Palestine. In addition, we shall use this case as the very first nucleus for the upcoming gastroschisis management in our referral hospital because the SSA yields a reduced hospital stay which is fundamental to our institution due to the limited number of beds and lower management costs to the hospital and families.